Colletotrichum gloeosporioides on cabbage in Pernambuco state, Brazil - Lima, Dêbora Maria Massa (Pesquisa Agropecuaria Brasileira, 2014)
Anthracnose of cabbage caused by Colletotrichum gloeosporioides Penz. was observed by the first time in Gravatá and Camocim de São Félix, Pernambuco, Brazil. This species was isolated in potato-dextrose-agar from the affected parts. Its pathogenicity was confirmed on cabbage after 20 days of inoculation with a suspension of Tween 80 at 0,02% with 105conidia/ml.